2019
DOI: 10.3389/fevo.2019.00048
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Invasive Rats in New Zealand

Abstract: Two species of invasive rats (Rattus norvegicus and R. rattus) arrived in New Zealand with Europeans in the mid to late eighteenth and nineteenth century respectively. They rapidly spread across the main islands of New Zealand and its offshore islands, displacing the historically introduced R. exulans. Today both species are widespread although the distribution of the subdominant R. norvegicus is patchy. Tissue samples were obtained from 425 R. rattus and 130 R. norvegicus across the New Zealand archipelago an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…We designed the rat primers to sit within mitochondrial regions conserved between Rattus rattus and Rattus norvegicus. We expected to find that the majority of amplified D-loop variation in Sydney samples of both of these species to be similar to those recorded in a recent study of the mitochondrial genetic diversity of both species across New Zealand, because the diversities present in the two neighbouring countries are likely to be similar (Russell et al 2019). Similarly, we designed the mouse primers to sit within regions of the mitochondrial Dloop conserved between the three subspecies of Mus musculus (M. m. musculus, M. m. domesticus, and M. m. castaneus), amplifying the majority of D-loop variation recorded in recent studies of mice from New Zealand and Australia (King et al 2016;Veale et al 2018).…”
Section: Dna Extraction and Amplificationmentioning
confidence: 76%
See 2 more Smart Citations
“…We designed the rat primers to sit within mitochondrial regions conserved between Rattus rattus and Rattus norvegicus. We expected to find that the majority of amplified D-loop variation in Sydney samples of both of these species to be similar to those recorded in a recent study of the mitochondrial genetic diversity of both species across New Zealand, because the diversities present in the two neighbouring countries are likely to be similar (Russell et al 2019). Similarly, we designed the mouse primers to sit within regions of the mitochondrial Dloop conserved between the three subspecies of Mus musculus (M. m. musculus, M. m. domesticus, and M. m. castaneus), amplifying the majority of D-loop variation recorded in recent studies of mice from New Zealand and Australia (King et al 2016;Veale et al 2018).…”
Section: Dna Extraction and Amplificationmentioning
confidence: 76%
“…In the haplotype network (Figure 2) we have included the six R. norvegicus haplotypes labelled 1-6 identified in New Zealand by (Russell et al 2019). Haplotypes 1, 2 and 6, recorded only in New Zealand, are uncoloured, so as to facilitate later discussions of connections between the two countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This northern origin may explain the late start (thirteenth century AD) of global range expansion (Figure 1e); [ 27 ] first toward SEA and coastal ports, then into the Middle East and Europe via trade networks, and finally globally to western Africa, eastern North America, South America, and New Zealand. [ 28,29 ] Rats also expanded from the ancestral range eastward into China, Russia, and eventually to western North America. [ 28,30 ] Analyses from South Africa have identified multiple introductions, both from European [ 22 ] and an unknown source population.…”
Section: Introductionmentioning
confidence: 99%
“…Today the ship rat is the dominant species in New Zealand, with the Norway rat patchily distributed across the mainland and some offshore islands (Russell et al 2019). King et al (2011) found this was largely due to different foraging strategies as explained by the Marginal Value Theorem (MVT) (Charnov, 1976).…”
Section: List Of Tablesmentioning
confidence: 99%